Unraveling Novel Mechanisms of Neurodegeneration Through a Large-Scale Forward Genetic Screen in Drosophila - Deal, Samantha L.; Yamamoto, Shinya (Frontiers in Genetics, 2019)
Neurodegeneration is characterized by progressive loss of neurons. Genetic and environmental factors both contribute to demise of neurons, leading to diverse devastating cognitive and motor disorders, including Alzheimer’s and Parkinson’s diseases in humans. Over the past few decades, the fruit fly, Drosophila melanogaster, has become an integral tool to understand the molecular, cellular and genetic mechanisms underlying neurodegeneration. Extensive tools and sophisticated technologies allow Drosophila geneticists to identify and study evolutionarily conserved genes that are essential for neural maintenance. In this review, we will focus on a large-scale mosaic forward genetic screen on the fly X-chromosome that led to the identification of a number of essential genes that exhibit neurodegenerative phenotypes when mutated. Most genes identified from this screen are evolutionarily conserved and many have been linked to human diseases with neurological presentations. Systematic electrophysiological and ultrastructural characterization of mutant tissue in the context of the Drosophila visual system, followed by a series of experiments to understand the mechanism of neurodegeneration in each mutant led to the discovery of novel molecular pathways that are required for neuronal integrity. Defects in mitochondrial function, lipid and iron metabolism, protein trafficking and autophagy are recurrent themes, suggesting that insults that eventually lead to neurodegeneration may converge on a set of evolutionarily conserved cellular processes. Insights from these studies have contributed to our understanding of known neurodegenerative diseases such as Leigh syndrome and Friedreich’s ataxia and have also led to the identification of new human diseases. By discovering new genes required for neural maintenance in flies and working with clinicians to identify patients with deleterious variants in the orthologous human genes, Drosophila biologists can play an active role in personalized medicine.